School Principals Practices in Holding Teachers Accountable for Curriculum Implementation: Insight from Ethiopian Public Primary Schools - Beyessa, Feyera; Kenea, Ambissa (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2023)
The study aims to explore school principals’ practices on management accountability relationship for curriculum implementation. An exploratory qualitative case study type and multiple case study research design were employed. A purposive sampling technique was used. The study’s findings affirm that school principals’ practices through management accountability relationships were compromised for classroom curriculum implementation yet, strongly operational to hold teachers accountable for subordinate tasks namely, improving students' scores by 5 to 10% from the previous year's average score, increasing enrollment rate, students’ promotion by 100%, reducing dropout rate. Lowering teachers’ efficiency results, in removal from promotion and salary increments were exercised for performing subordinate tasks as strong accountability measures. If the physical presence of teachers were realized in the schools or classrooms, teachers’ weakness in the implementation of curriculum did not invite rigorous penalty rather principals exercised their management accountability relationship by giving advice, oral warning, ongoing professional training, and transferring to the lower grade levels were the actual accountability measures exercised in the schools. Penalties like a series of fines of up to three months' salary, downgrading, and dismissal from the job were exercised for teachers’ code of ethics such as smoking, unreasonable absenteeism, addiction to alcohol, and others.